PENGARUH FINANCIAL DISTRESS, UKURAN PERUSAHAAN, DAN LEVERAGE PADA KONSERVATISME AKUNTANSI - Noviantari, Ni Wayan; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
The financial report is a picture of a company's performance. Management is given flexibility in choosing accounting methods to be used one by applying the accounting conservatism. The purpose of this study was to determine the effect of financial distress, the size of the company, and leverage on accounting conservatism. Manufacturing companies listed in Indonesia Stock Exchange became the population in this study by the research period 2010-2013. The number of samples analyzed 241 years of the company. Samples were taken with stratified random sampling.Teknik method of analysis used is multiple linear regression analysis technique. The results of this study indicate that the negative impact of financial distress on accounting conservatism, the positive effect of firm size on accounting conservatism, and leverage a negative effect on accounting conservatism.
Keywords: Financial Distress; Firm Size; Leverage; Accounting Conservatism